Canine and feline vestibular syndrome - POLIZOPOULOU (Ζ. Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ) Z. S.; DANOURDIS (Α. Μ. ΔΑΝΟΥΡΔΗΣ) A. M.; KOUTINAS (Α. Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
Signs of vestibular dysfunction (head tilt, asymmetric ataxia, spontaneous nystagmus, unilateral falling and rolling) are characteristic enough to be easily recognized without difficulty, even by inexperienced clinicians. Further differentiation between the peripheral (inner ear, vestibular nerve) and the central (vestibular nuclei, cerebellar peduncles, fastigial nucleus and flocculonodular lobe of the cerebellum) vestibular system should be based on a thorough history and an astute neurological examination. Affected animals should be reevaluated by serial neurological reexaminations to improve the accuracy of the initial assessment. Concomitant neurological signs, such as spastic hemiparesis or tetraparesis, proprioceptive déficits, other cranial nerve dysfunction and/or behavioral changes are indicative of central than peripheral vestibular syndrome. Apart from the minimum data base (complete blood count, serum biochemistry, urinalysis), the diagnostic evaluation should also include otoscopy, plain radiography of tympanic bullae (peripheral vestibular lesions), ear CT, brain MRI and cererebrospinal fluid analysis (central vestibular lesions). The present review first describes the clinical features of the vestibular syndrome from a differential point of view, regarding its neuroanatomical origin and secondly the most common conditions primarily characterized by vestibular dysfunction in the dog and cat.